Diversity of Opinion and Financing of New Technologies - Allen, Franklin; Gale, Douglas (Journal of Financial Intermediation, 1999)
The objective of this paper is to compare the effectiveness of financial markets and financial intermediaries in financing new industries and technologies in the presence of diversity of opinion. In markets, investors become informed about the details of the new industry or technology and make their own investment decisions. In intermediaries, the investment decision is delegated to a manager, who is the only one who needs to become informed, which saves on information costs, but investors may anticipate disagreement with the manager and be unwilling to provide funds. Financial markets tend to be superior when there is significant diversity of opinion and information is inexpensive. Journal of Economic Literature Classification Numbers: G1, G2.